Write-rite: Enhancing Handwriting Visualization Proficiency in Dysgraphic Children - Norsafinar Rahim (Journal of Computing Research and Innovation)
Dysgraphia is a significant and age-inconsistent difficulty developing writing skills among students. To address this issue, various intervention methods for developing writing skills in dysgraphic students have been implemented. However, previous studies on these intervention methods do not encompass all stages of writing skills, from basic levels to automatization. This creates a research gap, especially the lack of support to enhance writing visualization aided by technology. The study emphasized the importance of offering instructional support to educators, thereby enabling the proficient utilization of technology-assisted resources to aid dysgraphic children. By integrating this application, the research endeavoured to augment both the productivity and enjoyment inherent in the teaching and learning processes. The functionality of dysgraphic students' writing support applications would be more effective with the presence of Interaction Design (IxD) guidelines that is crucial to developing user-friendly writing support software. Dysgraphic-customized application, Write-rite, integrates IxD to improve visualization, motor control, and letter memory. Write-rite utilizes tracing exercises, animations, and repetition to enhance letter formation. The study, involving five dysgraphic students aged 8-12, employs Handwriting Legibility Scale for evaluation. The prototype is evaluated before, during, and after an eight-week intervention. Results indicate significant improvements in letter formation, motor skills, and overall handwriting legibility. The efficacy of this intervention offers dysgraphic students a tailored approach to improving handwriting skills. It emphasizes the importance of early intervention and specific strategies in alleviating writing challenges, thereby positively impacting students' cognitive skills and handwriting automation.